Conventional Practice of use of Cotton Bud in External Auditory Canal and it’s Complications - Rashid, Md Harun or; Uddin, Md Mojib; Hossain, Sheikh Md Rafiqul; Taous, Ahmmad (Bangladesh Journal of Otorhinolaryngology, 2022)
Objectives: To find out the complications arise from use of cotton bud in external auditory canal. Methods: This cross sectional study was carried out from January 2020- December 2020 in Pabna medical college hospital. About 100 patients with complications of cotton bud use were included in this study. Diagnosis was based on the history and otoscopic examination. Results: In this study most of the cases were age group 0-10 years -30%, 10-50-years 30%, 50-60- years 10%, more than 60 years 40%. Common Complications were Infection of external auditory canal 50%, injury to external auditory canal 40% and injury to tympanic membrane 10%. Conclusion: Injudicious use of Cotton bud has injurious effect for external auditory canal and should be avoided. Bangladesh J Otorhinolaryngol 2022; 28(1): 91-95